Conversion of Orange and Pineapple Fruit Peel Waste into Single Cell Protein Using Saccharomyces Cerevisiae - Clement Abiodun Abodunde; Bukola Catherine Akin-Osanaiye (Food, Agriculture and Natural Resources - NETWORKS, 2023)
The biological treatment of fruit wastes into single-cell protein has the potential to address the global protein shortage problem by producing a cost-effective product for food and feed. Pollution may be reduced if the substrate was made from the leftovers from the food processing industry. Herein, the submerged fermentation method was to make single-cell protein from pineapple and orange peels. Results indicated that fruit wastes analysed were highly hydrolysable. Proximate analysis of fruit wastes protein content of orange peel (10.73±0.02%) was significantly higher (P<0.05) than the protein content of pineapple peels (7.50±0.016%). When Saccharomyces cerevisiae was cultivated on fruit hydrolysate medium (FHM) without supplementation, the proportion of protein in single-cell protein was substantially lower, which produced (41.50±0.05% and 37.97±0.006%) total carbohydrate with (29.73±0.031% and 34.50±0.4%) crude protein, in both pineapple and orange medium respectively. The introduction of glucose to the supplemented fruit hydrolysate medium (GSFHM), increased the level of protein (45.50±0.031 and 37.73±0.011%) within the yeast cell, the comparison of treatment showed P<0.05, thus we can conclude that there is significant difference in the overall comparison of treatments in most of the parameters. The ITS2 region sequence analysis of Saccharomyces cerevisiae MA851180, revealed 99% identity with Saccharomyces cerevisiae. Thus, Saccharomyces cerevisiae produces higher amount of Single Cell Protein by submerged fermentation of pineapple peel hydrolysate as compared to orange peel hydrolysate. Hence, the single cell protein production by yeast depends on the growth substrates or media composition. SCP from yeast using fruit waste can serve as cheaper alternative to the conventional protein gotten from plant and animal and by selecting the most suitable prospective microbe and cost-effective technique.